THE Knowledge and Attitudes of Nurses Toward Polycystic Ovary Syndrome (PCOS) in the Hospitals of District Bahawalpur - Abdul Rehman; Khan, Nawshad Ali; Kanwal, Ayesha; Ahmad, Zaeem; Umm e Aiman; Asghar, Rubab; Ismail, Saima; Batool, Irsa (Indus Journal of Bioscience Research, 2025)
Introduction: Polycystic Ovary Syndrome (PCOS) is a common endocrine disorder impacting women’s reproductive, metabolic, and psychological health, yet awareness and management among healthcare professionals, especially nurses, remains inadequate. Study Purpose: The aim of the present study to determine the Level of Knowledge and attitude related to PCOS among nurses of District Bahawalpur. Methodology: Cross sectional descriptive study. The study was conducted on 150 staff nurses from different hospitals of district Bahawalpur in the Punjab province of Pakistan in 2025. The data was collected by using tested questionnaire to analyze nurses knowledge and attitude in the form of figure, tables, percentage and frequencies. Results: There were 122 female nurses (81.3%) and 28 male nurses (18.7%) among the valid responses. The majority of responders 138(92%) had heard about PCOS and hence have excellent knowledge about PCOS. From 138 nurses, 18(13%) have heard from their friends, 28(20.43%) have heard from mass media and majority 92(66.66%) have heard from health educators. Menstrual troubles 54(47.3%), obesity 12(10.52%), excess hair 5(4.38%) and delayed pregnancy 43(37.7%) were among the most prevalent issues mentioned by the respondents who were aware of PCOS-related problems. Conclusion: This study shows that nursing personnel in the hospitals of district Bahawalpur have a usually high degree of awareness of PCOS. Significant understanding of PCOS-related problems, treatment options, and linked systemic disorders was shown by the nurses. Despite this knowledge, the study found that there is a considerable stigma attached to the illness, which affects individual’s readiness to share their diagnosis.